Clinical guidelines «Rational use of nonsteroidal anti-inflammatory drugs (NSAIDs) in clinical practice» - A. E. Karateev; E. L. Nasonov; N. N. Yakhno; V. T. Ivashkin; N. V. Chichasova; L. I. Alekseeva; Yu. A. Karpov; M. A. Evseev; M. L. Kukushkin; A. B. Danilov; O. V. Vorobyeva; A. V. Amelin; et al. (Современная ревматология, 2015)
The paper presents the new version of the clinical guidelines «Rational use of nonsteroidal anti-inflammatory drugs (NSAIDs) in clinical practice » prepared by the Association of Rheumatologists of Russia, the Russian Pain Society, the Russian Gastroenterological Association, the Russian Society of Cardiology, the Association of Traumatologists and Orthopedists of Russia, the Association of Interdisciplinary Medicine, and the Russian Association of Palliative Medicine.In our country, NSAIDs are the most important and most popular class of analgesics. Unlike global practice, Russian physicians rather rarely recommend paracetamol as a first-line drug to relieve moderate or severe pain, by giving preference to NSAIDs; the use of opioid analgesics for noncancers is minimized because of tight legal restrictions.NSAIDs are effective and easy-to-use; however, they are far from safe; the administration of these medications may lead to serious gastrointestinal, cardiovascular, renal, and other complications in a number of cases. So the use of NSAIDs should be compulsorily monitored for adverse reactions and the choice of a specific drug for each clinical case should be based on the objective estimation of a ratio of its efficacy to safety.In recent years, there have been fresh data on the use of NSAIDs for different diseases and a few novel representatives of this drug group have appeared on the Russian pharmacological market.This all has necessitated a new version of the guidelines on the rational use of NSAIDs. These are based on the provisions that have high validity and have been confirmed by the results of well-organized clinical and large-scale population-based studies, as well as by their meta-analysis.The guidelines are intended for physicians of all specialties.